2018
DOI: 10.1021/acs.est.8b01140
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Transformation of the Iodinated X-ray Contrast Medium Iopromide, Its Aerobic Transformation Products, and Transfer to Further Iodinated X-ray Contrast Media

Abstract: The iodinated X-ray contrast medium (ICM) iopromide and its aerobic transformation products (TPs) are frequently detected in the effluents of wastewater treatment plants and in different compartments of the aquatic environment. In this study, the anaerobic transformation of iopromide and its aerobic TPs was investigated in water-sediment systems. Iopromide, its final aerobic TP didespropanediol iopromide (DDPI), and its primary aniline desmethoxyacetyl iopromide (DAMI) were used as model substances. Five biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…In approximately this depth, oxygen was depleted (oxygen concentration <1 mg/l). This coincidence indicates redox sensitive degradation of respective TrOCs and was, for example, observed and also previously reported for iomeprol and iopromide (Redeker et al, 2018;Schulz et al, 2008;Zhang et al, 2019). Furthermore, acesulfame, 4-formylaminoantipyrine, metoprolol (Burke et al, 2014), benzotriazole, bezafibrate, gabapentin, and methylbenzotriazole were previously reported to be better attenuated under oxic/suboxic conditions which is in agreement with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…In approximately this depth, oxygen was depleted (oxygen concentration <1 mg/l). This coincidence indicates redox sensitive degradation of respective TrOCs and was, for example, observed and also previously reported for iomeprol and iopromide (Redeker et al, 2018;Schulz et al, 2008;Zhang et al, 2019). Furthermore, acesulfame, 4-formylaminoantipyrine, metoprolol (Burke et al, 2014), benzotriazole, bezafibrate, gabapentin, and methylbenzotriazole were previously reported to be better attenuated under oxic/suboxic conditions which is in agreement with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…The highest removal rate constants were calculated for the iodinated X-ray contrast agents iomeprol (IOM) and IOP. Complete deiodination of both compounds in saturated sediments has only been observed under anoxic redox conditions, but both compounds are known to readily loose side chains of the iodinated ring structure under aerobic conditions. , It is therefore likely that the high removal rates calculated in the present study are due to transformation of both compounds and do not represent complete mineralization. Removal of the artificial sweetener ACS, the lipid-lowering agent bezafibrate (BZF), the anticorrosive agents benzotriazole (BTA) and methylbenzotriazole (MBT), and the anticonvulsant GAB along oxic to suboxic (i.e., denitrifying) flow paths in hyporheic sediments has previously been described in laboratory column experiments , and observed in the HZ .…”
Section: Resultsmentioning
confidence: 67%
“…The highest removal rate constants were calculated for the iodinated X-ray contrast agents iomeprol (IOM) and IOP. Complete deiodination of both compounds in saturated sediments has only been observed under anoxic redox conditions, 45 but both compounds are known to readily loose side chains of the iodinated ring structure under aerobic conditions. 46,47 It is therefore likely that the high removal rates calculated in the present study are due to transformation of both compounds and do not represent complete mineralization.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For example, Kong et al studied the degradation of IPM by using UV/chlorine, by comparing with UV or chlorine alone 10 , and they found that in contrast to chemical processes, biochemical methods have limited pollutants removal efficiency. For instance, it took over 20 days to achieve more than 95% of IPM degradation by using anaerobic process 11 .…”
Section: Introductionmentioning
confidence: 99%